2016
DOI: 10.1111/jcpp.12507
|View full text |Cite
|
Sign up to set email alerts
|

Annual Research Review: Enduring neurobiological effects of childhood abuse and neglect

Abstract: Background and Scope Childhood maltreatment is the most important preventable cause of psychopathology accounting for about 45% of the population attributable risk for childhood onset psychiatric disorders. A key breakthrough has been the discovery that maltreatment alters trajectories of brain development. This review aims to synthesize neuroimaging findings in children who experienced caregiver neglect as well as from studies in children, adolescents and adults who experienced physical, sexual and emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
758
2
25

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 973 publications
(815 citation statements)
references
References 262 publications
(468 reference statements)
30
758
2
25
Order By: Relevance
“…The evidence for the sensitive period in the Luby et al report (1) should not imply that hippocampal structure is no longer plastic beyond the preschool period, but simply that it no longer appears to reflect the influence of maternal support. Indeed, there is evidence for greater effects of childhood maltreatment on a hippocampal structure in later compared with earlier childhood (7,8), and perhaps even later for effects on the prefrontal cortex (7). A sensitive period for an environmental influence on neurodevelopment must thus be A B Fig.…”
Section: Sensitive Periodsmentioning
confidence: 99%
“…The evidence for the sensitive period in the Luby et al report (1) should not imply that hippocampal structure is no longer plastic beyond the preschool period, but simply that it no longer appears to reflect the influence of maternal support. Indeed, there is evidence for greater effects of childhood maltreatment on a hippocampal structure in later compared with earlier childhood (7,8), and perhaps even later for effects on the prefrontal cortex (7). A sensitive period for an environmental influence on neurodevelopment must thus be A B Fig.…”
Section: Sensitive Periodsmentioning
confidence: 99%
“…These associations emerged from planned comparisons of regions reportedly affected by sleep loss and an exploratory analysis of regions of interest previously identified as affected by maltreatment (Teicher & Samson, 2016; Teicher et al, 2016) and corrected for multiple comparisons. Further, sleep efficiency was found to mediate the association between maltreatment and measures of whole hippocampal and hippocampal subfield volumes, and volume of inferior frontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The most consistent findings are smaller midsagittal area or decreased fractional anisotropy of the corpus callosum and lower hippocampal volume in adults but not necessarily in youths (see Teicher and Samson, 2016; Teicher, Samson, Anderson, and Ohashi, 2016, for recent reviews). Maltreatment is also associated with attenuated development of the anterior cingulate, orbitofrontal and dorsolateral prefrontal cortex, and with enhanced amygdala response to threatening stimuli and reduced striatal response to reward (Teicher & Samson, 2016; Teicher et al, 2016). …”
Section: Introductionmentioning
confidence: 95%
“…cortex has been reported with witnessing domestic violence and thinning of the sensory cortical area for genitalia with sexual abuse [2]. These structural changes, especially the ones specific to a certain type of adversity, may be adaptive in the face of expected future adversity and seem to extend to all individuals exposed to adversity and not dependent on the development of psychopathology per se.…”
mentioning
confidence: 99%
“…A series of studies have shown that exposure to adverse life events, especially when occurring in childhood, can lead to lasting biological changes that impact the function of several key systems. Brain imaging studies have reported lasting structural changes in adults exposed to childhood trauma in a number of brain regions [2]. These changes appear to be more or less specific to the type of experienced adversity.…”
mentioning
confidence: 99%